Behavioral Intentions Of Bank Customers - Irawan Fakhrudin Mahalizikri; Ungsi Antara Oku Marmai; Elda Martha Suri (JPS (Jurnal Perbankan Syariah), 2020)
The understanding of the people of the Bengkalis Island especially towards sharia banking services is still low. The purpose of this study was to analyze the factors that influence bank customers' switching behavior intentions. This research method uses a quantitative approach and data collection using a questionnaire given to 150 bank customers taken by non-probability sampling and analyzed using SPSS version 16. The results of hypothesis testing indicate that attitudes, subjective norms, perceptions of behavioral control, and ease of the system and the procedure has a positive and significant effect on the intention to switch bank customers, while the social influence and the influence of the image of the bank does not affect the intention to switch bank customers. This research is relevant for management to design service products that make it easy for users to increase user intentions to transact on Islamic banks.